2015
DOI: 10.1039/c5cp01870f
|View full text |Cite
|
Sign up to set email alerts
|

Surface behavior of amphiphiles in aqueous solution: a comparison between different pentanol isomers

Abstract: Position isomerism is ubiquitous in atmospheric oxidation reactions. Therefore, we have compared surface-active oxygenated amphiphilic isomers (1-and 3-pentanol) at the aqueous surface with surface-and chemically sensitive X-ray photoelectron spectroscopy (XPS), which reveals information about the surface structure on a molecular level. The experimental data is complemented with molecular dynamics (MD) simulations. A concentration-dependent orientation and solvation of the amphiphiles at the aqueous surface is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 63 publications
2
62
0
Order By: Relevance
“…A tot saturates. As discussed earlier, 35 the trend of the curve can be interpreted as a result of the adsorption of alcohols at the aqueous surface with increasing bulk concentration and, finally, the formation of a monolayer-like structure (ML) in the surface region. Here, the term monolayer refers to a closely packed layer of amphiphilic molecules at the liquid-vapor interface that has approximately a thickness of a single molecular length, i.e.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…A tot saturates. As discussed earlier, 35 the trend of the curve can be interpreted as a result of the adsorption of alcohols at the aqueous surface with increasing bulk concentration and, finally, the formation of a monolayer-like structure (ML) in the surface region. Here, the term monolayer refers to a closely packed layer of amphiphilic molecules at the liquid-vapor interface that has approximately a thickness of a single molecular length, i.e.…”
Section: Resultsmentioning
confidence: 82%
“…All acquired spectra were evaluated regarding the total area A tot of the liquid phase C 1s photoelectron (PE) signal (A tot = A(C C ) + A(C OH )) and the PE intensity ratio R between the two liquid phase C 1s peak areas (R = A(C C ) / A(C OH )). As discussed in more detail before, 35 the PE signal A tot can be used as a measure for the amount of solutes at the solution interface, while the PE intensity ratio R between the peak areas of C C and C OH reveals information about the orientation of these molecules in the surface region. The binding energy is sensitive to their local chemical and physical environment, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because XPS is traditionally performed in ultrahigh vacuum, measurements with liquid samples have been limited to a few instruments worldwide [20][21][22][23][24]. Recently, however, we demonstrated that aqueous suspensions of nanoparticles (colloids) can be passed within a liquid microjet through the x-ray beam, enabling the unique analytical capabilities of XPS to be extended to aqueous NP dispersions [25].…”
Section: Introductionmentioning
confidence: 99%